A cohort study of factors influencing breastfeeding in regional Western Australia - Cox, Kylee Nicole (Curtin University, 2016)
Factors influencing breastfeeding initiation and duration in regional Western Australia were examined in this cohort study, with 427 mothers and their infants followed from birth to 12 months. Whilst 98% of mothers initiated breastfeeding after birth, less than 6% were still exclusively breastfeeding at six months. Positive influences on breastfeeding duration included baby-friendly hospital practices, antenatal education and positive attitudes towards breastfeeding, while prepregnancy smoking and overweight were negatively associated with breastfeeding duration.